Payoff or penalty? A comparison of the marriage wage differential for men and women across 15 nations - Claudia Geist (Luxembourg Income Study (LIS), 2006)
This paper contributes to a broader understanding of the role of marriage in gender stratification from a comparative perspective by providing important descriptive evidence of the distribution of the marriage wage gap for men and women crossnationally. This paper focuses on marital status and men's and women's wages in fifteen countries using Wave V of the Luxembourg Income Study (LIS). Examining whether there are systematic wages differences between married and unmarried individuals, I find clear evidence of a wage advantage for married men but mixed results for women; Results suggest that both selection into marriage and, to a much more limited extent, household structure are relevant in accounting for some of the wage advantages of married men as well marriage wage gaps found for women. Differences in human capital and household structure explain differences in the wages between married and unmarried women in nine of the fifteen countries, but only in one country for men. For men, the variation in the marriage wage gap net of human capital and household context is limited; for women it varies widely. Explorations seeking to link the variation in the wage differential with macro level indicators such as fertility or female labor force participation do not suggest that these aspects of context play a determining role in the marriage wage gap.
Keywords: 330; Lohnstruktur; Familienplanung; Familienökonomik; Welt